Histomolecular phenotypes and outcome in adenocarcinoma of the ampulla of vater - Chang, David K; Jamieson, Nigel B; Johns, Amber L; Scarlett, Christopher J; Pajic, Marina; Chou, Angela; Pinese, Mark; Humphris, Jeremy L; Jones, Marc D; Toon, Christopher; Nagrial, Adnan M; Chantrill, Lorraine A; et al. (Journal of clinical oncology, 2013)
Individuals with adenocarcinoma of the ampulla of Vater demonstrate a broad range of outcomes, presumably because these cancers may arise from any one of the three epithelia that converge at that location. This variability poses challenges for clinical decision making and the development of novel therapeutic strategies. We assessed the potential clinical utility of histomolecular phenotypes defined using a combination of histopathology and protein expression (CDX2 and MUC1) in 208 patients from three independent cohorts who underwent surgical resection for adenocarcinoma of the ampulla of Vater. Histologic subtype and CDX2 and MUC1 expression were significant prognostic variables. Patients with a histomolecular pancreaticobiliary phenotype (CDX2 negative, MUC1 positive) segregated into a poor prognostic group in the training (hazard ratio [HR], 3.34; 95% CI, 1.69 to 6.62; P < .001) and both validation cohorts (HR, 5.65; 95% CI, 2.77 to 11.5; P < .001 and HR, 2.78; 95% CI, 1.25 to 7.17; P = .0119) compared with histomolecular nonpancreaticobiliary carcinomas. Further stratification by lymph node (LN) status defined three clinically relevant subgroups: one, patients with histomolecular nonpancreaticobiliary (intestinal) carcinoma without LN metastases who had an excellent prognosis; two, those with histomolecular pancreaticobiliary carcinoma with LN metastases who had a poor outcome; and three, the remainder of patients (nonpancreaticobiliary, LN positive or pancreaticobiliary, LN negative) who had an intermediate outcome. Histopathologic and molecular criteria combine to define clinically relevant histomolecular phenotypes of adenocarcinoma of the ampulla of Vater and potentially represent distinct diseases with significant implications for current therapeutic strategies, the ability to interpret past clinical trials, and future trial design.